2020
DOI: 10.2351/7.0000077
|View full text |Cite
|
Sign up to set email alerts
|

Real-time prediction of quality characteristics in laser beam welding using optical coherence tomography and machine learning

Abstract: Laser beam welding significantly outperforms conventional joining techniques in terms of flexibility and productivity. The process benefits, in particular, from the highly focused energy and thus from a well-defined heat input. The high intensities of brilliant laser radiation, however, induce very dynamic effects and complex processes within the interaction zone. The high process dynamics require a consistent and reliable quality assurance to ensure the required weld quality. A novel sensor concept for laser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…In addition to evaluating the capillary depth, the OCT signal can be utilized to assess correlations between the course of the weld depth and the process stability. The hypothesis that the course of the measured capillary depth correlates with the process stability during laser beam welding could already be confirmed in [22]. Therefore, in further investigations, it can be evaluated analogously to what extent a correlation between mutations in the OCT signal and the distribution of process pores can be found.…”
Section: Correlation Between µCt Images and Process Monitoring Sensor Signalsmentioning
confidence: 80%
“…In addition to evaluating the capillary depth, the OCT signal can be utilized to assess correlations between the course of the weld depth and the process stability. The hypothesis that the course of the measured capillary depth correlates with the process stability during laser beam welding could already be confirmed in [22]. Therefore, in further investigations, it can be evaluated analogously to what extent a correlation between mutations in the OCT signal and the distribution of process pores can be found.…”
Section: Correlation Between µCt Images and Process Monitoring Sensor Signalsmentioning
confidence: 80%
“…It could be demonstrated that the interferometric measuring principle, applied coaxially to the laser beam, enables a measurement of the capillary depth during deep penetration welding [21]. In addition to the determination of the penetration depth, the quality of the weld seam surface concerning the occurrence of irregularities in the topography could be determined based on the measured capillary depth [22].…”
Section: Online Process Monitoring In Laser Beam Weldingmentioning
confidence: 99%
“…Optical coherence tomography (OCT) is an interferometric measurement technology that enables the inline measurement of weld seam topography coaxially to the processing laser in a scanning optic [7][8][9][10][11]. For instance, Hartung et al [11] combined an OCT with external highspeed video camera measurements for the identification of spatters which represent height deposits on the workpiece surface.…”
Section: Introductionmentioning
confidence: 99%